NEPRILYSIN INHIBITORS (ARNI) IN THE TREATMENT OF CHRONIC HEART FAILURE — A SYSTEMATIC REVIEW AND CRITICAL APPRAISAL OF THE EVIDENCE - Marcin Schulz; Karolina Osińska; Dawid Studziński; Michał Kulczak; Anna Kołcz; Agnieszka Morawa (International Journal of Innovative Technologies in Social Science, 2026)
Angiotensin receptor–neprilysin inhibitors (ARNI), with sacubitril/valsartan as the prototypical agent, have fundamentally transformed the pharmacological treatment paradigm of chronic heart failure (HF) [6,11,36,47,48,49,50]. This systematic review synthesizes the available clinical evidence, with a particular focus on the therapeutic efficacy of ARNI across the full continuum of left ventricular ejection fraction [3,4,17,50]. In patients with heart failure with reduced ejection fraction (HFrEF), pivotal randomized trials have consistently demonstrated the superiority of ARNI over conventional angiotensin-converting enzyme inhibitors in lowering cardiovascular mortality and HF-related hospitalizations, while also promoting favorable reverse myocardial remodeling [2,9,10,11,18,26,30,39,41,43,44,49]. In contrast, among individuals with preserved or mildly reduced ejection fraction, the principal clinical benefit is reduction in recurrent HF hospitalizations, with numerically greater treatment effects reported in women [1,3,7,18,23]. In addition, sacubitril/valsartan exhibits clinically relevant renoprotective effects and a favorable safety profile in complex patient populations, including those with diabetes mellitus or advanced chronic kidney disease [4,10,11,18]. Contemporary clinical guidelines position ARNI as a cornerstone of quadruple guideline-directed medical therapy, recommending early initiation during hospitalization and proactive dose up-titration to optimize clinical outcomes [7,8,11,13,21,31,47,48,49,50]. Addressing barriers to implementation—such as treatment-related hypotension and therapeutic inertia—remains essential to reduce the considerable global burden of heart failure [5,7,28,29,34,38].